2018
DOI: 10.1038/s41598-018-33867-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of sagittal alignment and skeletal muscle mass in patients with spinal degenerative disease

Abstract: We investigated how skeletal muscle mass (SMM) affects spinal sagittal balance (radiographic parameters) in symptomatic spinal patients. The first purpose of this study was to evaluate the body composition and the spinal sagittal alignment in symptomatic spinal patients. The second purpose of this study was to compare whether the body composition and the spinal sagittal alignment is different in patients with cervical spine disease and lumbar spine disease. We retrospectively evaluated 313 patients who were ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…Radiographic parameters of interest included sagittal balance (C7-SVA), cervical lordosis (CL; C2–C7), lumbar lordosis (LL; L1–S1), thoracic kyphosis (TK; T5–T12), pelvic incidence (PI), pelvic tilt (PT), and sacral slope (SS) [17, 18]. The C7-SVA was determined by the horizontal offset between a plumb line drawn from the center of C7 and the posterosuperior corner of the S1 endplate.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic parameters of interest included sagittal balance (C7-SVA), cervical lordosis (CL; C2–C7), lumbar lordosis (LL; L1–S1), thoracic kyphosis (TK; T5–T12), pelvic incidence (PI), pelvic tilt (PT), and sacral slope (SS) [17, 18]. The C7-SVA was determined by the horizontal offset between a plumb line drawn from the center of C7 and the posterosuperior corner of the S1 endplate.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the DLS group, the spinal sarcopenia subgroup exhibited inferior results in a timed up and go test and had poorer Oswestry disability index scores compared with the non-spinal sarcopenia subgroup. Regarding patients with degenerative spinal diseases, studies have indicated that the pelvic tilt angle is the sagittal parameter most closely related to skeletal muscle mass [45]. Skeletal muscle mass might be a crucial factor related to the posterior inclination of the pelvis in symptomatic patients with spinal conditions, especially cervical spine disease.…”
Section: Progression and Characteristics Of Spinal Sarcopeniamentioning
confidence: 99%
“…In recent years, several original articles have discussed how spinal sarcopenia influences spinal parameters in individuals, including cervical lordosis, thoracic kyphosis, and lumbar lordosis [43][44][45][46]. Notably, these spinal changes often lead to pathologic conditions such as degenerative scoliosis and compression fractures which are associated with poor life quality compared to their normal counterpart [46].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more attention is often paid to sagittal balance than coronal balance during spinal deformity assessment, surgical plan-making, and surgical procedure. Generally, sagittal imbalance results in increased muscular effort and energy expenditure, causing pain, fatigue, and disability [5]. Sagittal imbalance of the spine as a crucial factor in the pathogenesis of myelopathy is supported by several reports [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Multiple studies have described normative values for parameters of spinopelvic alignment in different populations of varying ages and pathologic conditions. In these studies, the interrelation of pelvic parameters, LL, TK, sagittal imbalance, and its effect on the quality of life and patient outcome has been well-established [5,8,9]. Many studies have reported that pelvic incidence (PI), a constant morphological parameter in each individual, has a significant influence on sagittal alignment of the lumbar spine or the thoracic spine, such as LL and TK [10].…”
Section: Introductionmentioning
confidence: 99%